Application of RLGC modeling in probing the electrical properties of monolayer graphene at microwave frequencies. Issue 15 (13th October 2018) - Patel, Kamlesh; Sharma, Pulkit
Abstract: The S-parameters of the microstrip line loaded with graphene on glass and graphene on quartz as a superstrate are measured from 10 MHz to 26.5 GHz. These parameters have shown only a little difference compared to glass or quartz loaded microstrip line. Then, de-embedded S-parameters of superstrate loaded microstrip line are modeled as the transmission line (RLGC) parameters and these parameters are obtained with frequency. Their comparison with unloaded microstrip line shows large changes in R and G whereas, in L and C parameters, no significant changes have been noticed with superstrates. In these parameters, larger percentage changes for graphene on glass have showed a poor contact between two than graphene and quartz. Changes in R and G parameters confirmed that graphene has modified the surface resistance and effective relative permittivity on loading the microstrip line.